Kinematic Characteristic Analysis of Hypoid Gear based on Two Kinds of Eigenfunction - Bingyang Wei; Ke Zhang; Bo Zhang; Yuliang Guo (Jixie chuandong)
Based on the classical space meshing theory， two kinds of basic eigenfunctions and eigenvectors of conjugate surfaces are defined. The function of the two kinds of eigenfunctions in the analysis of the meshing characteristics of conjugate surfaces is described. The expression of the parameters related to the meshing motion of conjugate surfaces is presented. Two kinds of characteristic functions are used in the meshing motion characteristics study of hypoid gears， and the analysis of influence laws of cutter head radius on the tooth surface suction speed， slide-to-roll ratio and comprehensive curvature radius is carried out. The results show that a smaller cutter radius is more beneficial to improve the contact and lubrication performance of the gear pair. It lays a foundation for further topological design and meshing performance control of tooth surface.